General Collective Intelligence vs the Innate Collective Intelligence Factor - Williams, Andy (My University, 2020)
INTRODUCTION: Groups of individuals of species exhibiting collective behaviours have been suggested to have some innate general collective intelligence. General Collective Intelligence or GCI has been described as a platform that organizes individual humans into a single collective intelligence with the potential capacity for exponentially greater general problem-solving ability. OBJECTIVES: To explore whether a functional modelling approach might have the capacity to represent any system of organization resulting in a general collective intelligence factor. And to explore what functionality might be required for a GCI to exponentially increase it. METHODS: An analysis of the meaning of general problem-solving ability in the functional state space of a system of cognition or collective cognition is used to assess whether GCI has the potential to exponentially increase increase that ability. RESULTS: GCI has the potential to exponentially increase increase impact on all general outcomes where limited by general problem-solving ability CONCLUSION: While an innate general collective intelligence factor might exist, and while conventional CI solutions might have significant impact on specific collective outcomes, a GCI is required to exponentially general problem-solving ability, and therefore to exponentially increase collective outcomes. This capacity has the potential to be disruptive.
Keywords: General Collective Intelligence; Human-Centric Functional Modelling; Artificial General Intelligence